Experimental and theoretical study of the intramolecular C–H···N and C–H···S hydrogen bonding effects in the 1H and 13C NMR spectra of the 2‐(alkylsulfanyl)‐5‐amino‐1‐vinylpyrroles: a particular state of amine nitrogen. (22nd May 2013) - Afonin, Andrei V.; Pavlov, Dmitry V.; Albanov, Alexander I.; Tarasova, Ol'ga A.; Nedolya, Nina A.
<x xml:space="preserve">Abstract</x> In the 1H NMR spectra of the 1‐vinylpyrroles with amino‐ and alkylsulfanyl groups in 5 and 2 positions, an extraordinarily large difference between resonance positions of the HA and HB terminal methylene protons of the vinyl group is discovered. Also, the one‐bond 1J(Cβ, HB) coupling constant is surprisingly greater than the 1J(Cβ, HA) coupling constant in pyrroles under investigation, while in all known cases, there was a reverse relationship between these coupling constants. These spectral anomalies are substantiated by quantum chemical calculations. The calculations show that the amine nitrogen lone pair is removed from the conjugation with the π‐system of the pyrrole ring so that it is directed toward the HB hydrogen. These factors are favorable to the emergence of the intramolecular C–HBN hydrogen bonding in the s‐cis(N) conformation. On the other hand, the spatial proximity of the sulfur to the HB hydrogen provides an opportunity of the intramolecular C–HBS hydrogen bonding in the s‐cis(S) conformation. Presence of the hydrogen bond critical points as well as ring critical point for corresponding chelate ring revealed by a quantum theory of atoms in molecules (QTAIM) approach confirms the existence of the weak intramolecular C–HN and C–HS hydrogen bonding. Therefore, an unusual high‐frequency shift of the HB signal and the increase in the 1J(Cβ, HB) coupling constant can be explained by the effects of hydrogen bonding. Copyright © 2013 John Wiley & Sons, Ltd.